A STUDY TO ASSESS THE EFFECTIVENESS OF STRUCTURED TEACHING PROGRAMME ONKNOWLEDGE REGARDING NEUROLOGICAL AND PHYSICAL GROWTH ANDDEVELOPMENT OF PRETERMBABIES AMONGMOTHERS OF PRETERMADMITTED INNICUOFSELECTEDHOSPITALS AT AKLERA (Indo-American Journal of Life Sciences and Biotechnology, 2021)
The goal of this study is to find out how much mothers of preterm babies know about their children'sneurological and physical growth and development. through an organised teaching programmeatAklera'sNirogdham Hospital and Research Center. An experimentation-free approach was adopted inthe study. In this study, participants filled out a self-structured knowledge questionnaire in two parts. Asociodemographic questionnaire was employed in the first part of the study, while a self-structuredknowledge questionnaire was used in the second part of the study. The data was analysed usingdescriptive and inferential statistical methods. It was shown that 60% of preterm mothers had excellentknowledge about preterm children's neurological and physical development, compared to 40% of thosewho had adequate knowledge. As a consequence, nurses were instructed to provide information toexpectant women about their children's neurological and physical development.